2007
DOI: 10.1186/1475-2859-6-17
|View full text |Cite
|
Sign up to set email alerts
|

Production of surfactin from Bacillus subtilis MZ-7 grown on pharmamedia commercial medium

Abstract: Background: Commercial medium (Pharmamedia) was investigated for the production of surfactin by Bacillus subtilis MZ-7. Different media (defined, semi-defined, and complex media) were compared for the production of surfactin after fixing the least influential variables in standardized fermentation conditions. Carbohydrate and nitrogen supplements were also tried to improve production in Pharmamedia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 66 publications
0
42
1
1
Order By: Relevance
“…Bacteriocins produced by Gram-positive bacteria, especially Bacillus spp., have attracted worldwide attention because of their great potential as food preservatives, therapeutic agents, and biosurfactants (in the case of lipopeptides) (13,14,15). Though many bacteriocins or bacteriocin-like inhibitory substances (BLIS) in the genus Bacillus have been reported (e.g., cerein, produced by Bacillus cereus Gn105 [16], and cerein 7, produced by B. cereus Bc7 [17]), screening of naturally occurring habitats in different parts of the world could lead to isolation of peptide-producing microorganisms having potential antimicrobial activity.…”
mentioning
confidence: 99%
“…Bacteriocins produced by Gram-positive bacteria, especially Bacillus spp., have attracted worldwide attention because of their great potential as food preservatives, therapeutic agents, and biosurfactants (in the case of lipopeptides) (13,14,15). Though many bacteriocins or bacteriocin-like inhibitory substances (BLIS) in the genus Bacillus have been reported (e.g., cerein, produced by Bacillus cereus Gn105 [16], and cerein 7, produced by B. cereus Bc7 [17]), screening of naturally occurring habitats in different parts of the world could lead to isolation of peptide-producing microorganisms having potential antimicrobial activity.…”
mentioning
confidence: 99%
“…It has been reported that the addition of iron, magnesium or manganese to the culture medium increased biosurfactant production by B. subtilis isolates (Thimon et al, 1992;Chu, 1998, 2002;Al-Ajlani et al, 2007). Mn 2+ at a concentration 0.01 mM increased biosurfactant production by B. subtilis ATCC 21332 from 0.33 to 2.6 g/l (Wei and Chu, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, this is the first report describing biosurfactant production by B. subtilis using CSL as culture medium. The amount of biosurfactant produced (about 1.3 g/l) was close to the values reported by other authors using different substrates.It has been reported that the addition of iron, magnesium or manganese to the culture medium increased biosurfactant production by B. subtilis isolates (Thimon et al, 1992; Chu, 1998, 2002;Al-Ajlani et al, 2007). Mn 2+ at a concentration 0.01 mM increased biosurfactant production by B. subtilis ATCC 21332 from 0.33 to 2.6 g/l (Wei and Chu, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Each family has a specific number of amino acids, but with different residues at specific positions. It also has different lengths and isomery of β-hydroxyl fatty acids (cis, trans, iso and anteiso, etc), that is, lipopetides have a remarkable heterogeneity of molecular weight and isomery [10][11][12][13][14]. One way of reducing bioproduction cost is by using low cost nutrients as culture medium (fermentation) such as industrial waste or by-product, for instance, glycerol from the biodiesel industry.…”
Section: Introductionmentioning
confidence: 99%